Sex hormone-mediated change on muscle activation deactivation dynamics in young eumenorrheic women - Soedirdjo, Subaryani D. H.; Rodriguez, Luis A.; Chung, Yu-Chen; Casey, Ellen; Dhaher, Yasin Y. (Frontiers in Physiology, 2023)
The goal of the study was to characterize muscle activation/deactivation dynamics across the menstrual cycle in healthy young women. Twenty-two healthy eumenorrheic women (age: 27.0 ± 4.4 years; mean ± SD) were tested every other day for one menstrual cycle. Serum estradiol and progesterone were quantified at the time of testing. Peak torque (PT), time to peak torque (TPT), and half relaxation time (HRT) of soleus muscle twitch were measured. Muscle twitch was elicited by delivering 1 ms width electrical pulses to the tibial nerve at an intensity that generated a maximum motor response (S-100) and at supramaximal intensity (S-120; 1.2 × S-100). The analyses were performed for each menstrual cycle phase: 1) the follicular phase to analyze the effect of estradiol while the progesterone concentrations remained at low concentrations; 2) the luteal phase to analyze the effect of progesterone with background estradiol concentrations. In the follicular phase, there was no association of estradiol for PT, TPT, and HRT. In the luteal phase, while estradiol had no association on PT, TPT, and HRT, progesterone expressed a significant association with HRT reduction but no association on PT or TPT. Also, there was a significant estradiol and progesterone interaction for HRT. However, the regression parameters are nearly zero, suggesting that the change in HRT may not have an impact on muscle performance across the menstrual cycle but implications on other women’s health conditions with elevated sex hormone concentrations, such as pregnancy, may prove critical.